Sustainability in the mining industry: An evaluation of the National Planning Commission's diagnostic overview - Zvarivadza, T. (Elsevier, 2022)
Environmental stewardship is the keystone to sustainability in mining and industry. While environmental compliance appears to be costly at first sight, it gives a mining company a competitive edge. Several pieces of legislation have been enacted as a means to deal with impacts of mining on the environment and hence provide an enabling environment for sustainable development (SD). The industry has adopted the principles of environmentally responsible mining, in line with the recommendations of international bodies like the International Organization for Standards (ISO), The Equator Principles Association and International Finance Corporation (IFC). This paper evaluates the sustainability of the South African mining industry in the light of the National Planning Commission (NPC)’s overview that ‘South Africa's growth path is highly resource-intensive and hence unsustainable.’ Arguments are presented to refute this viewpoint and additional impacts of mining on the environment, not mentioned by the NPC, are also discussed together with the measures that the mining industry has taken to resolve such impacts. Although the mining industry has instituted emergency preparedness measures, environmental incidents do occur, but these isolated incidents do not provide evidence that mining is unsustainable. Such events are a feature of all sectors of the economy. The author advocates the establishment of a SD legal framework through consultative discussions with interested and affected parties to create an environment conducive for legal compliance, which would include SD indicators to enable the Department of Minerals and Resources to monitor company compliance and identify defaulting companies.